The enhanced healing of a high‐risk, clean, sutured surgical incision by prophylactic negative pressure wound therapy as delivered by Prevena™ Customizable™: cosmetic and therapeutic results - Scalise, Alessandro (Int Wound J, 2014)
According to the literature, incisional closure complications may range from postoperative surgical site infections, representing 17–22% of health care‐associated infections, surgical wound dehiscence and formation of haematomas or seromas, and can lead to delayed or impaired incision healing. These kinds of situations are more common when wounds are closed under tension or in specific patient morbidities. Obesity, in particular, is associated with an impaired blood flow to tissues, predisposing the patient to increased risk of wound complications by various mechanisms. Incisional complications can become relevant economic burdens for health care systems because of an increase in the average length of hospital stay and readmissions, and additional medical and surgical procedures. Thus, a preventive therapy may have a critical role in the management of healing. Negative pressure wound therapy (NPWT) technology as delivered by Prevena™ Customizable™ (Kinetic Concepts Inc., San Antonio, TX) has recently been the focus of a new investigation, as a prophylactic measure to prevent complications via immediate postoperative application in high‐risk, clean, closed surgical incisions. The authors present a 62‐year‐old class II obese female, who underwent bilateral inguinal dermolipectomy. Prophylactic NPWT as delivered by Prevena™ was performed successfully over surgical incisions. Cosmetic and therapeutic results are shown.